Val av liggplats och väderskydd hos dikor vid utedrift vintertid - Johansson, Emma (2010)
If you keep cattle in a herd outside all year round on big varying grounds, their possibility to perform their natural behaviour increases. This way of keeping cattle requires that you provide them with their other needs, like shelter and a dry and clean resting place. According to the animal welfare authority´s regulations on livestock farming, only animals that are suited to stay outside during the cold season are allowed to be kept outside. They should also have access to a shelter or another building that gives them protection from the weather and wind and provides a dry and clean resting place.